2001
DOI: 10.1111/j.1349-7006.2001.tb01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Reduces Hormone Responsiveness of Human Breast Cancer Cells

Abstract: Resistance to hormonal therapy frequently occurs following successful treatment in breast cancer. The mechanism responsible for this acquired resistance is still unknown. It has been suggested that a hypoxic tumor microenvironment promotes malignant progression of cancer, i.e., hypoxia may promote estrogen-independent growth (a more malignant phenotype) of breast cancer. To clarify this hypothesis, the effects of hypoxia on the growth responses to hormonal agents and the expression levels of estrogen receptor ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 15 publications
7
48
1
3
Order By: Relevance
“…In a multivariate analysis, HIF-1a was the only independent variable, which predicted ERa negativity. This is consistent with cell culture studies where intermittent hypoxia induces proteasome-dependent downregulation of ERa (Kurebayashi et al, 2001;Cooper et al, 2004;Yi et al, 2009). This is also supported by immunohistochemical studies on ERa-positive tumours where the geographic distribution of CAIX, a surrogate marker of hypoxia, corresponds to areas of tumour negative for ERa (Cooper et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…In a multivariate analysis, HIF-1a was the only independent variable, which predicted ERa negativity. This is consistent with cell culture studies where intermittent hypoxia induces proteasome-dependent downregulation of ERa (Kurebayashi et al, 2001;Cooper et al, 2004;Yi et al, 2009). This is also supported by immunohistochemical studies on ERa-positive tumours where the geographic distribution of CAIX, a surrogate marker of hypoxia, corresponds to areas of tumour negative for ERa (Cooper et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…This is in concordance with earlier published data, 35 but apart from the association to the cell cycle, this could also indicate that HIF-1a expression is correlated to a certain type of breast cancer with proliferative features and frequent overexpression of cyclin E. 36,37 HIF-1a has not been previously explored in relation to treatment prediction in a randomised treatment trial, but one breast cancer cell line study has demonstrated that hypoxia induces tamoxifen-resistant growth. 24 In our study we could not confirm this link between hypoxia and tamoxifen response, and both HIF1a low and high tumours appeared to respond to tamoxifen treatment. Since there is a negative association between ER and HIF1a expression, the amount of ER-positive and HIF-1a high tumours was rather small in our study, which might have affected the results.…”
Section: Discussioncontrasting
confidence: 54%
“…19 From studies of breast cancer cell lines, it appears that hypoxia also correlates to loss of ER expression [20][21][22][23] and that this may induce tamoxifenresistant growth. 24 Hormone independent growth is frequently caused by abnormalities in growth factor signalling pathways such as EGFR, HER2, MAPK-signalling via ERK1/2, or IGFR via PI3K, 25 all of which may be influenced by HIF-1a. HIF-1a has also been implicated as an independent prognostic marker in both lymph node-negative 26 as well as lymph node-positive breast cancers.…”
mentioning
confidence: 99%
“…Initially, we treated hypoxic cells with tamoxifen (1.0 mM) for 48 h during hypoxic and normoxic conditions, whereupon the cell-cycle phase distribution was evaluated by flow cytometry. The anti-estrogen response differed substantially between normoxic and hypoxic samples, as partially detailed earlier (Kurebayashi et al, 2001). As illustrated in Figure 3a and b, there was an 18% increase in G 0 /G 1 cells in tamoxifen treated normoxic cells, after 48 h, but only a 9% G 0 /G 1 accumulation with tamoxifen during hypoxia (see Figure 3b, P-values were calculated using Student's ttest).…”
mentioning
confidence: 66%